Feature extraction using Bat Algorithm for Brain Cancer - Khanjar, Rajaa.J. (International Journal of Psychosocial Rehabilitation, 2020)
The brain is a very essential part of the human body. The brain is composed of soft nervous tissue in the skull that helps vertebrates to perform various functions. Cancer is a complex and delicate disease that requires us to know if a person is infected or not quickly because not knowing leads to the death of a person. In this paper, the tumor will be extracted by extracting the strong characteristics of the brain after the process of extraction of the important area. This is done using a bat algorithm, which is one of the smart methods that give the optimal solution for each generation that has been generated. Thus, after extracting the strong characteristics of the tumor can be employed in any way to find out if the person is infected or not.